Answer:
![-2+1+6+13+22+...=\sum(n^2+2n-2)](https://tex.z-dn.net/?f=-2%2B1%2B6%2B13%2B22%2B...%3D%5Csum%28n%5E2%2B2n-2%29)
Step-by-step explanation:
<u>Series in Summation Notation</u>
We must try to find a general formula for each term and then use summation to generalize the sum of all the terms for any value of n, the term number.
The series is
![-2+1+6+13+22+...](https://tex.z-dn.net/?f=-2%2B1%2B6%2B13%2B22%2B...)
The difference between consecutive terms will be computed:
![a_2-a_1=1-(-2)=3](https://tex.z-dn.net/?f=a_2-a_1%3D1-%28-2%29%3D3)
![a_3-a_2=6-1=5](https://tex.z-dn.net/?f=a_3-a_2%3D6-1%3D5)
![a_4-a_3=13-6=7](https://tex.z-dn.net/?f=a_4-a_3%3D13-6%3D7)
We can see that
![a_{n+1}-a_n=2n+1](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D-a_n%3D2n%2B1)
Applying summation on both sides:
![\sum [a_{n+1}-a_n]=\sum (2n+1)=\sum 2n+\sum 1](https://tex.z-dn.net/?f=%5Csum%20%5Ba_%7Bn%2B1%7D-a_n%5D%3D%5Csum%20%282n%2B1%29%3D%5Csum%202n%2B%5Csum%201)
Knowing that
![\displaystyle \sum n=\frac{n(n+1)}{2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csum%20n%3D%5Cfrac%7Bn%28n%2B1%29%7D%7B2%7D)
![\sum [a_{n+1}-a_n]=n(n+1)+n=n^2+2n](https://tex.z-dn.net/?f=%5Csum%20%5Ba_%7Bn%2B1%7D-a_n%5D%3Dn%28n%2B1%29%2Bn%3Dn%5E2%2B2n)
Similarly, the sum of the left side is found to be
![\sum [a_{n+1}-a_n]=a_{n+1}-a_1](https://tex.z-dn.net/?f=%5Csum%20%5Ba_%7Bn%2B1%7D-a_n%5D%3Da_%7Bn%2B1%7D-a_1)
Replacing into the above equation, we find
![a_{n+1}-a_1=n^2+2n](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D-a_1%3Dn%5E2%2B2n)
Solving
![a_{n+1}=n^2+2n+a_1=n^2+2n-2](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%3Dn%5E2%2B2n%2Ba_1%3Dn%5E2%2B2n-2)
Having the general term, the series is expressed as
![-2+1+6+13+22+...=\sum(n^2+2n-2)](https://tex.z-dn.net/?f=-2%2B1%2B6%2B13%2B22%2B...%3D%5Csum%28n%5E2%2B2n-2%29)
For n=0 to infinity